Adding Core Stability Exercise After SWD and TENS Treatment Reduces Pain in Patients with Non-Specific Low Back Pain - Lina Pratifi; Sugiono, Sugiono; M. Mudatsir Syatibi (Jurnal Keterapian Fisik, 2023)
Background: Non-specific low back pain (LBP) is pain in the lower back that has no specific pathological cause, characterized by tenderness and muscle spasm that reduces lumbar stability. Common therapies in healthcare facilities include Short Wave Diathermy (SWD) and Transcutaneous Electrical Nerve Stimulation (TENS). However, effectiveness can be increased by adding Core Stability Exercise (CSE), which focuses on strengthening the core muscles to maintain spinal stability. This study aims to determine the effectiveness of adding CSE after SWD and TENS in reducing pain in patients with non-specific LBP. Methods: This study used a quasi-experimental design with a two-group pre-test and post-test design. The study sample consisted of 30 patients with non-specific LBP at Bethesda Hospital in Yogyakarta, who were selected using purposive sampling according to inclusion and exclusion criteria. Group I received SWD and TENS, while group II received SWD, TENS, and CSE twice a week for four weeks. The research instrument was the Visual Analogue Scale (VAS). Data analysis was performed using the paired sample t-test and independent sample t-test. Results: Analysis showed a p-value <0.001 in both groups, with greater pain reduction in the group that received additional CSE. Conclusion: The addition of Core Stability Exercise after SWD and TENS therapy was effective in reducing pain in patients with non-specific LBP. It is recommended that physiotherapists integrate core stability exercises as part of standard therapy to reduce pain and improve lower back stability.